2014
DOI: 10.1152/ajplung.00353.2013
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial epithelial injury in the context of alloimmunity promotes lymphocytic bronchiolitis through hyaluronan expression

Abstract: Epithelial injury is often detected in lung allografts, however, its relation to rejection pathogenesis is unknown. We hypothesized that sterile epithelial injury can lead to alloimmune activation in the lung. We performed adoptive transfer of mismatched splenocytes into recombinant activating gene 1 (Rag1)-deficient mice to induce an alloimmune status and then exposed these mice to naphthalene to induce sterile epithelial injury. We evaluated lungs for presence of alloimmune lung injury, endoplasmic reticulum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Other possible mechanisms include mitochondrial transfer to rescue stressed cells and improve cellular bioenergetics and function to allow for more efficient repair, as has been elegantly demonstrated previously [44] . Oxidative stress of lung epithelium has been demonstrated in humans with OB after lung transplant and in mice with induced alloimmune activation [45] , [46] , [47] . In addition, we have previously shown that the lungs are under oxidative stress after BMT in our mouse model and that this could be normalized by treatment with KGF, a factor typically secreted by MSCs [48] .…”
Section: Discussionmentioning
confidence: 99%
“…Other possible mechanisms include mitochondrial transfer to rescue stressed cells and improve cellular bioenergetics and function to allow for more efficient repair, as has been elegantly demonstrated previously [44] . Oxidative stress of lung epithelium has been demonstrated in humans with OB after lung transplant and in mice with induced alloimmune activation [45] , [46] , [47] . In addition, we have previously shown that the lungs are under oxidative stress after BMT in our mouse model and that this could be normalized by treatment with KGF, a factor typically secreted by MSCs [48] .…”
Section: Discussionmentioning
confidence: 99%
“…Pep-1 efficiently inhibited dendritic cell-dependent cluster formation, IL-2 and IFN-γ production, and T cell proliferation [299]. Moreover, Pep-1 ameliorated naphthalene-induced lymphocytic bronchitis in a mouse model [300]. …”
Section: Ha As Therapeuticmentioning
confidence: 99%
“…( 36 ). HA cables have been induced in a variety of cell types in vitro , including smooth muscle cells from the lung ( 37 ) and colon ( 32 ), in airway ( 38 ) and renal epithelial cells ( 39 ), as well as epidermal keratinocytes ( 40 ). However, HA cables have yet to be described in vivo , although HA and IαI co-staining has been reported in a human case of inflammatory bowel disease ( 32 ).…”
Section: The Different Forms Of Hamentioning
confidence: 99%